The effect of YF3 on the mechanical properties and low-temperature degradation of 3Y-TZP ceramics. Issue 18 (15th December 2019) - Jing, Qiang; Bao, Jinxiao; Ruan, Fei; Song, Xiwen; An, Shengli; Zhang, Yonghe; Tian, Zhen; Xie, Min; Gao, Jianquan
Abstract: The low-temperature degradation and mechanical properties of 3Y-TZP- x YF3 ceramics synthesized by a conventional solid-state reaction were investigated. The addition of YF3 has a significant effect on the aging and mechanical properties of 3Y-TZP ceramics. The results show that the mechanical properties and aging resistance of 3Y-TZP- x YF3 ceramics with slow grain growth are greatly improved when the content of YF3 is maintained in a reasonable biphasic region (RBR) due to the dominant role of T-M (tetragonal to monoclinic). When the content of YF3 exceeds 0.15 mol%, the mechanical properties and aging properties of ceramics in a saturated biphasic region (SBR) decrease due to the influence of T-C (tetragonal to cubic). More importantly, 3Y-TZP-0.15YF3 ceramics have good aging resistance and mechanical properties, and YF3 doping makes the application of 3Y-TZP in dental ceramics more meaningful.